Effects of Sophora flavescens aiton and the absorbed bioactive metabolite matrine individually and in combination with 5-fluorouracil on proliferation and apoptosis of gastric cancer cells in nude mice - Hu, Huan-Fu; Wang, Zheng; Tang, Wen-Li; Fu, Xue-Ming; Kong, Xiang-Jun; Qiu, Ying-Kun; Xi, Sheng-Yan (Frontiers in Pharmacology, 2022)
Sophora flavescens Aiton (SFA) and its main bioactive component matrine are widely used in TCM preparations and have achieved good curative effects for the treatment of various tumors. However, the mechanisms underlying SFA and matrine individually and in combination with chemotherapeutic drugs for treatment of gastric cancer (GC) remain unclear. In order to elucidate the mechanisms underlying the ability of SFA and matrine individually and in combination with chemotherapeutic drugs to inhibit proliferation and promote apoptosis of human GC cells, forty-eight nude mice were randomly divided into six groups that were treated with normal saline (model group), 5-fluorouracil (5-FU), SFA decoction (SFAD), matrine, SFAD+5-FU, or matrine+5-FU. A subcutaneous heterotopic tumor model was established in nude mice by implantation of human GC BGC-823 cells. All mice were treated for 28 days. Bioactive components in SFA were determined by HPLC-MS/MS. The tumor volume and weight, and inhibition rate of mice were documented. Histopathology and ultramicroscopic pathology of tumor tissues were observed. The tumor cell cycle and apoptosis in vivo were detected. Serum levels of PCNA, BAX, Bcl-2, Caspase-3 and cleaved Caspase-3, protein levels of tumor MS4A10, MS4A8, MS4A7, PCNA, BAX, Bcl-2, Caspase-3, and cleaved Caspase-3 were measured. Results showed both SFAD and matrine inhibited the growth of transplanted GC cells, which was more effective when combined with 5-FU. The tumor inhibition rates of the 5-FU, SFAD, matrine, SFAD+5-FU, and matrine+5-FU groups were 53.85%, 33.96%, 30.44%, 59.74%, and 56.55%, respectively. The body weight of nude mice was greater in the SFAD group than the normal saline and matrine groups. SFAD+5-FU and matrine+5-FU blocked BGC-823 cells in the G0-G1/S transition, promoted apoptosis, and significantly decreased the content of serum apoptosis-inhibitory proteins (PCNA and Bcl-2) as well as protein expression of MS4A8, MS4A10, Bcl-2, and PCNA in tumor tissues, while increasing serum levels of pro-apoptotic proteins (Caspase-3 and cleaved-Caspase-3) and protein expression of BAX and cleaved-Caspase-3 in tumor tissues. SFAD and matrine both individually and in combination with 5-FU ameliorated malignancy of transplanted tumors by reducing proliferation and promoting apoptosis of BGC-823 cells. These findings confirm the anti-tumor synergistic effect of TCM and chemotherapeutic drugs.